A new measurement protocol to differentiate sources of halitosis. (3rd July 2016) - Aydin, Murat; Özen, Murat Eren; Evlice, Burcu; Ferguson, Matthew; Uzel, İlter
Abstract: Objective: Three sources of halitosis exist, potentially in any combination: mouth, nasal cavity or alveolar breath. There has been no universally accepted protocol which differentiates and quantifies each odour source separately. In this study a new gas measurement protocol is described and tested to determine whether each odour source can be separately detected without contamination. Materials and methods: Ninety healthy volunteers were divided into three groups. Hydrogen sulphide (H2 S), volatile organic compounds (VOCs) and hydrogen (H2 ) were artificially generated in the mouth, nose and pulmonary alveoli, respectively. VOC, ammonia (NH3 ), sulphur dioxide (SO2 ), H2 S and H2 gas readings from mouth, nose and alveolar air were measured and compared. Measurements were taken before and during gas generation. Results: Contamination of nasal air (2.8%) and alveolar air (5.0%) by oral H2 S; alveolar air (2.06%) and oral air (4%) by nasal organic gas; nasal air (18.43%) and oral air (9.42%) by alveolar H2 was calculated. Conclusion: The results demonstrated that artificially generated oral H2 S nasal VOC and alveolar H2 can be individually quantified. This gas measurement protocol can be used diagnostically or to gauge response to therapy in any medical or dental setting.